Comparison of a novel gamified binocular therapy and standard monocular patching therapy in treating unilateral amblyopia in young children: a prospective, multicenter, randomized controlled trial - Wenqing Zhu; Jiawei Zhang; Heying Zhang; Jianjuan Zhao; Jin Lin; Chanling Hu; Rui Liu (Trials)
Abstract Background Amblyopia is a leading cause of visual impairment in children, and conventional treatments often encounter challenges related to poor compliance and adverse psychosocial effects. Recent advancements in treatment approaches have evolved beyond merely suppressing the dominant eye, now focusing on improving binocular visual function. Binocular therapy has emerged as a promising and innovative approach. The study evaluates the efficacy of a novel gamified binocular therapy for treating unilateral amblyopia on comprehensive visual functions. Methods This prospective, multicenter, randomized, blinded, controlled trial is designed as a non-inferiority study. A total of 144 patients, aged 4 to 7 years, diagnosed with amblyopia, will be randomly assigned to either the intervention group (72 patients) or the control group (72 patients). Participants in the intervention group will engage in daily 1-h sessions of gamified binocular therapy, 5 days per week, for a total duration of 8 weeks (40 h). The treatment employs a roguelike shooting game, presented through binocular presentation via two distinct channels, powered by a real-time artificial intelligence-driven visual engine. The control group will receive traditional patching therapy for 2 h per day, 7 days per week for 8 weeks (112 h). The primary outcome measure of this study is distance visual acuity, while secondary outcome measures include stereoacuity and developmental visual perception assessed using the Developmental Test of Visual Perception (DTVP). These measures will be assessed at baseline and follow-up visits to determine the effectiveness of the intervention. Discussion This study is a multicenter randomized trial to evaluate the efficacy and safety of the Vision Planet Training System for the treatment of unilateral amblyopia in young children compared with standard monocular patching therapy. The results are anticipated to offer valuable insights into the efficacy of binocular treatment for unilateral amblyopia. Trial registration Chinese Clinical Trial Registry ChiCTR2300079090. Registered on 25 December 2023.  https://www.chictr.org.cn/showproj.html?proj=215374 .